Spontaneous bladder perforation with urinary ascites secondary to posterior urethral valves and suspected atypical congenital nephrotic syndrome of a premature neonate: A case report - Alicia Phillips; Miranda Floen; Teri Mauch; Claudia Berrondo (Urology Case Reports)
Fetal bladder rupture is a rare phenomenon with few reported cases in the literature. It is often a complication of congenital abnormalities causing urinary obstruction, such as posterior urethral valves (PUV). Congenital nephrotic syndrome (CNS) is another rare genitourinary disorder characterized by proteinuria, hypoalbuminemia and edema presenting in the first 3 months of life. We present a case of a premature male infant delivered at 32 weeks with fetal ascites from bladder rupture secondary to PUV. The infant also exhibited clinical features suggestive of CNS. This case illustrates the value of comprehensive differential diagnosis, medical decision making, and collaborative multidisciplinary care.